Legal construction and amendment to promote blockchain applications: International experiences and recommendations for Vietnam. - Do Quynh Anh; Pham Thi Tham; Pham Thi Linh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
The outstanding characteristics of blockchain technology, along with the prevalence of crypto assets, cryptocurrencies, and other applications of the technology can positively contribute to innovation, economic development, and breakthrough growth for Vietnam. Learning from developed countries when constructing and amending Vietnamese laws to promote blockchain technology applications is necessary. From a comprehensive study of regulatory approaches and legal frameworks amendment to promote blockchain applications in such countries as Japan, the United States, and the European Union, the authors suggest some recommendations for revising and amending the relevant legal documents in Vietnam. Code: 24102601